Ghost microscope imaging system from the perspective of coherent-mode representation. (14th February 2018) - Shen, Qian; Bai, Yanfeng; Shi, Xiaohui; Nan, Suqin; Qu, Lijie; Li, Hengxing; Fu, Xiquan
Abstract: The coherent-mode representation theory of partially coherent fields is firstly used to analyze a two-arm ghost microscope imaging system. It is shown that imaging quality of the generated images depend crucially on the distribution of the decomposition coefficients of the object imaged when the light source is fixed. This theory is also suitable for demonstrating the effects from the distance the object is moved away from the original plane on imaging quality. Our results are verified theoretically and experimentally.